What does cabin crew need during inflight emergencies? a SHELL-model analysis - Manikath, Elizabeth; Li, Wen-Chin; Piotrowski, Pawel (Springer, 2025)
Although flight attendants are responsible for the safety of millions of passengers per year, their safety role is publicly often trivialized. Extensive training is provided by the airlines to support cabin crew to handle emergencies, however, is the training sufficient to overcome the challenges flight attendants face? Technological evolutions to minimize errors in the cockpit can be found throughout the past century, however, most of the equipment which cabin crew are using are outdated and do not meet the requirements of today’s air travel. Research question: Following research questions will be addressed in this study: RQ1: Which challenges do cabin crew face during inflight emergencies? RQ2: How can cabin crew be supported during inflight emergencies? RQ3: How can technological aids, such as illumination, support cabin crew handling emergencies? Methodology: A qualitative study was conducted with 15 cabin crew members. Open-ended questions were asked to assess which challenges cabin crew face and how they can be supported during emergencies. The SHELL-model framework was used to analyze and categorize the open-ended questions. Results and Discussion: Major concerns were unruly passengers as well as panicking and uncontrollable behaviour. Fire and smoke were another concerns belonging to the Environment- Liveware interface. Improving flight attendant training with regards to duration, content, and frequency were highlighted as an effective measure to increase confidence in cabin crew applying their knowledge and skills. It was mentioned that trainings should be more realistic, such as using actors to mime anxious passengers. Conclusion: This study identified flight attendant’s challenges using the SHELL model framework. Flight attendants could gain more confidence in handling emergencies by improving the training frequency, duration and content. Technological aids such as smart and/or optimized emergency buttons could further improve discreet communication between flight attendants and cabin crew.
Keywords: Artificial Intelligence & Image Processing; 46 Information and computing sciences; cabin crew emergency processes; passenger safety; cabin crew training; SHELL Model Analysis; inflight emergency